A phenomenological study on exploring parental involvement among role model students of Sri Sempurna International School - Rode, Nigel Evan; Wong, Su Luan (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
The purpose of this qualitative phenomenological study was to understand the role that parents play and explore the extent of parental involvement among role model students in a private secondary school setting from the viewpoint of their children. Using a sample size of ten participants, the researcher collected data through interviews and a reflective journal. The research analysis was carefully conducted using the 7-step method of phenomenological analysis designed by Colaizzi (1978). The study found that in order to raise a generation of student role models, parental involvement is seen through the laying on of strong foundations which comes in the form of the upbringing of their children from young, and by giving them the freedom and space to learn, grow and mature as the child grows older, together with providing the best that the parents can offer towards their child’s education, in trusting that private education will continue to build upon that foundations that parents have laid upon.